A computational method of stress intensity factor for flat-oval cross-section thin-walled pipe. (March 2019) - Li, C.; Xie, L.Y.; Xie, Y.J.; Zhao, B.F.; Hu, Z.Y.; Zhao, H.F.; Yin, Wei
Abstract: As an important parameter of fracture criterion, stress intensity factor (SIF) is considered to be one metric of the singular stress field intensity near the crack tip, also a main parametric in fracture mechanics. Therefore, solving technique on the stress intensity factor takes an important role in engineering applications. In view of typical three-dimensional features of flat-oval thin-walled pipes, it is relatively tough to obtain the stress intensity factors for the special-shaped shells with multi-transverse cracks by classical methods. In this paper, a very simple method based on J 2 -integral and bending theory is proposed to calculate the SIFs. Examples demonstrate that this technique is feasible, especially, that, suitable for the determination of the stress intensity factors of three-dimensional complicated structures. And the results show that not only the solution process is simple and available, but also the closed-form solutions can be derived effectively.